A Correctional–Public Health Collaboration for Colorectal Cancer Screening in a State Prison System. (September 2021) - Dumont, Dora M.; Davis, Deborah; Sadacharan, Radha; Lamy, Eric; Clarke, Jennifer G.
Correctional facilities provide health care to large numbers of medically underserved people. As such, preventive health in correctional settings is an important yet underused investment in public health. Because they often have histories of poor access to health care, the justice-involved population is more likely than the general population to be diagnosed with advanced-stage cancers. We report on the first 2 years of an ongoing collaboration between a state correctional system and state health department to implement annual colorectal cancer screening for sentenced people using fecal immunochemical testing (FIT). Preparation for the annual iterations begins in January, and patient engagement begins in March. In the first year of implementation (2018), 1396 of 1856 (75.2%) sentenced people completed an eligibility screen, and 254 of 321 (79.1%) eligible patients completed a FIT (eligible patients were aged ≥50 [≥45 if Black] in year 1 [lowered to ≥45 in year 2] and reported no previous relevant medical or family history of colorectal cancer); 54 (21.3%) completed FITs were positive. Of the 54 patients with positive FITS, 33 (61.1%) completed follow-up colonoscopies resulting in the identification of polyps in 26 (48.1%) patients with a positive FIT. We found invasive adenocarcinoma for 2 (3.7%) of the positive FITs (6.1% of colonoscopies performed). In the second year (2019), after a conversion from paper to tablet-based eligibility screening, 1707 of 2059 (82.9%) sentenced people completed an eligibility screen, and 200 of 285 (70.2%) eligible patients completed a FIT, 27 (13.5%) of whom had a positive result. We share lessons learned about implementing mass screening to encourage further communication among departments of health and corrections to advance preventive health.